Исследование зависимости продолжительности перевозки и укладки бетонной смеси от её температуры - Абдел Хамид Хали Абу Саль, Аднан (Ways to Improve Construction Efficiency, 2013)
In article examine dependence of maximum assume longing of transporting and packing of concrete from it temperature.